The evolving role of radiation therapy in pediatric Hodgkin's disease. Issue 6 (2nd June 2016) - Fredman, Elisha; Mansur, David B.; Russo, Suzanne
ABSTRACT: Identifying the optimal treatment of pediatric Hodgkin's disease has been at the forefront of clinical investigation in recent years. Results of a number of large clinical trials have driven paradigm shifts in how physicians approach this often curable disease. In an effort to balance the goals of maximizing survival while minimizing acute toxicities and late complications, the recommended indications, targets, doses and schedules of chemotherapy and radiation have and continue to evolve. Recent attempts to decrease the total volume of tissue receiving radiation without requiring a significant escalation in cytotoxic chemotherapy have shown promise in low, intermediate and high risk patients. Utilizing risk-adapted, response-based treatment, researchers hope to uncover a subpopulation that may not require previously considered standard treatment modalities.